De Ulixis mentione, quam Cynaethus poeta fecisse videtur (H.AP. 167sq. AHS) - Pierzak, Damian (Collectanea Philologica, 2012)
In Homer the mythological events from outside the Trojan plot are usually referred to in the discourse of the characters and not by the narrator himself; this, however, is not the case in the Homeric Hymns. In the following short note, I shall attempt to suggest that the author of the Delian Hymn to Apollo could have alluded to Odysseus through a different narrative device. Both the language and structure (including the so-called ring composition) are examined in order to strengthen the present hypothesis.